ON THE IV CONGRESS OF ANESTHESIOLOGISTS AND EMERGENCY UZBEKISTAN AND XI REPUBLICAN SCIENTIFIC AND PRACTICAL CONFERENCE “ACTUAL PROBLEMS OF ORGANIZATION EMERGENCY MEDICAL CARE: QUESTIONS ANESTHESIOLOGY, INTENSIVE THERAPY IN CRITICALLY ILL” (Неотложная медицинская помощь)
On the IV Congress Of Anesthesiologists And Emergency Uzbekistan And XI Republican Scientific And Practical Conference “Actual Problems Of Organization Emergency Medical Care: Questions Anesthesiology, Intensive Therapy In Critically Ill”.